Penyuluhan Gizi dan Stunting serta Pemanfaatan Tepung Kulit Telur pada Kader Kesehatan di Kabupaten Sumedang - Yenni Zuhairini; Aly Diana; Dimas Erlangga Luftimas; Haidar Rizqi; Ayunda Jihadillah; Afini Dwi Purnamasari; Yeni Intan Kusuma Dewi Affandy; Dearly Ayu Zahrotun Haq; Ana Dina Sakinah; Dina Novtyana Puspita (Institut Pertanian Bogor, 2024)
Sumedang still struggles with a stunting problem; based on the 2022 Indonesian Nutrition Status Survey (SSGI), the percentage of stunted children in Sumedang is the highest among all cities in West Java. Health Cadres have a very potential role in stunting prevention from an early age, providing education about the importance and selection of healthy and balanced nutrition food during pregnancy and breastfeeding, and the utilization of alternative food ingredients to improve the quality of nutrition in family food when conducting activities carried out at the Posyandu. This activity aims to enhance health cadres' knowledge through nutrition and stunting education and encourage the utilization of eggshell flour in creating family food innovations to prevent stunting from an early age. This activity uses pre-test and post-test questionnaires for measuring cadres’ knowledge about balanced nutrition and stunting prevention and a food creation competition based on eggshell flour, which is evaluated based on five criteria: creativity, nutritional facts, taste, texture, and presentation/serving. This activity effectively enhanced the knowledge regarding balanced nutrition and stunting prevention, as indicated by a significant increase in the average score before and after the intervention, with a p-value of 0.005. Furthermore, the food creation competition demonstrated the substantial potential of eggshell flour in preparing a diverse range of nutritious family food, including both savory and sweet dishes/snacks. This activity improved health cadres' knowledge and expanded the variety of healthy food through the innovative utilization of eggshell flour.